Presence of heavy metals and microbiological quality of concentrates for pig feeding in four Colombian regions - Barrientos, Irina (2018)
The objective of this study was to evaluate the presence of heavy metals (arsenic, cadmium, mercury, and lead), Salmonella and E. coli, as well as mesophiles, fungi and yeast counts and Clostridium sulfite reductor count in concentrates for pigs in four regions of Colombia. Feed samples (n=38) were collected from 19 farms for the analysis of heavy metals. Samples were processed in triplicate and analyzed by plasma-coupled atomic absorption spectrometry. For the microbiological analysis, 391 samples from 22 farms were processed. For the detection of Salmonella, the MDS-3M equipment was used, and its presence was confirmed using Maldi-tof, while for the counting of E. coli cromocult agar was used. For mesophilic aerobes, the plate count agar was used and for the fungi and yeasts rose bengal agar. The results indicated that only two samples from the same farm had high arsenic values (2 ppm) while the other metals were within the expected limits. The counts of mesophiles, fungi and yeasts and Clostridium were within the Colombian regulations, with only one positive sample for Salmonella (0.25%), while 1% of the samples presented E. coli. The results reflect that the quality of concentrates used in pig feeding is not an important source of pathogens or heavy metals.